Goodbye, Mr. Terupt. (Mr. Terupt, vol. 4.) - Buyea, Rob (Mr. Terupt, 2020)
The kids discover their beloved Mr. Terupt is moving away at the end of the school year and begin hatching plans to make this year unforgettable.